The Efficiency of Learning Media in Building Student Character - Yves, Caers; Murat, Ritacco; Justine, Köse (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
At present the role of the teacher is very important for the creation of character in students. There are several elements that can support the formation of character learning for students. One of them is the accuracy in choosing learning media by the teacher in the learning process. This study aims to build student character by using appropriate and effective learning media. The method used in this study is a quantitative method using a survey model with Google Forms and in-depth interviews with one of the students. The results of this study can explain that implementing the efficiency of learning media in building character in students will present an effective and optimal learning process. The conclusion of this study is that the selection of appropriate instructional media will influence and have an effect on the learning process, which in building the character of current students really needs efficient media so that students can easily understand and apply it in the school, family and community environment. The limitations of this study are that researchers can only conduct research at the intermediate level, due to short time constraints, the researcher hopes that future researchers can conduct research at a higher level and in more depth.